Calculus Formation in Bladder from Migrated Intrauterine Devices - Mangkubumi Putra Wijaya; Kurnia Penta Seputra; Besut Daryanto; Taufiq Nur Budaya (Jurnal Kedokteran Brawijaya, 2022)
Migration of the intrauterine device (IUD) into the bladder has been a rare case. There were reported 31 cases of IUD migration into the bladder until 2006. Although IUD migration is asymptomatic, it should be removed to prevent complications such as pelvic abscess, bladder or intestinal rupture, and adhesion. A 52-year-old woman came to the urology clinic with pyuria since the previous 3 months. She had a history of IUD insertion in 1982; and two months later, she got pregnant. Since 2015, she has suffered from dysuria but has never been treated and has worsened in the past 3 months. On physical examination, tenderness was found in the suprapubic region. The results of urinalysis showed pyuria and hematuria. The ultrasonography findings, there were large bladder stones. An abdominal x-ray revealed the presence of a bladder stone with the IUD tail. Vesicolithotomy was performed and the IUD was found attached to an 11x7 cm bladder stone. The patient had a good postoperative condition without any special complications. The IUD in the bladder is a medium for forming secondary bladder stones. Most cases of IUD migration are caused by a lack of evaluation after the installation procedure. This case suggested that the physician should be more careful in carrying out the installation procedure. It is necessary to evaluate the location of the IUD after installation to prevent further patient complications.